The Effect of Applied Voltage in The Electrocoagulation Process of Reducing Pond and River Water Turbidity - Masthura Masthura (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Abstract : The study about the effect of the applied voltage to decrease the water turbidity from local pond and river have been conducted. This study aims to investigate the ability of the electrocoagulation process in removing pollutants containing groundwater from the pond and river. The water sample obtained from Dusun I Paya Perupuk Tanjung Pura in Langkat Regency. Indonesia which has been reported having high water turbidity. A copper plate was used as a sacrificial electrode with a specific variation of applied voltage of 6, 9, and 12 Volts. The result showed that applying 9 and 12 volts of voltages were able to reduce 60% and 66% of water turbidity from water pond, respectively. In river water, both optimum applied voltages could reduce approximately 98% of water turbidity. The result indicated that the electrocoagulation process potentially devoted as an alternative way to treat the massive local groundwater.Abstrak : Penelitian mengenai pengaruh tegangan listrik terhadap penurunan kekeruhan air sumur dan air sungai pada proses elektrokoagulasi telah dilakukan. Penelitian ini bertujuan untuk mengetahui kemampuan proses elektrokoagulasi dalam menghilangkan polutan yang berada di air yang diperoleh dari air sumur dan air sungai. Sampel air diperoleh dari Dusun I Desa Paya Perupuk Tanjung Pura Kabupaten Langkat. Lapisan plat tembaga (Cu) digunakan sebagai elektroda dengan variasi spesifik voltase sebesar 6, 9, dan 12 volts. Hasil menunjukkan bahwa pemberian voltase 9 dan 12 dapat menurunkan kekeruhan air sumur sebesar 60 dan 66%. Pada sample air sungai, pemberian kedua voltase optimum dapat menurunkan 98% dari kekeruhan air. Hasil penelitian mengindikasikan proses elektrokoagulasi berpotensi sebagai sebuah cara alternative untuk mengolah air.